2020
DOI: 10.1152/japplphysiol.00280.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in muscle architecture and neuromuscular fatigability induced by isometric resistance training at short and long muscle-tendon unit lengths

Abstract: Eight weeks of isometric training at a long or short muscle-tendon unit length increased and did not change fascicle length, respectively. The “width” of the torque-angle relationship plateau became broader following isometric training at the long length. Despite marked differences in muscle architecture and functional adaptations between the groups, there was only a small-magnitude improvement in neuromuscular fatigue resistance, which was surprisingly negatively related to increased fascicle length in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 75 publications
(92 reference statements)
1
24
1
Order By: Relevance
“…Lichtwark et al 47 determined a positive relationship between passive tibialis anterior fascicle length and sarcomere length; 2.64 µm is the average optimal sarcomere length 48 ; and 15° PF is close to the average optimal angle for dorsiflexion force production. 49 Based on these characteristics, the fascicle length adaptations (measured at 15° PF) in our study equated to a serial sarcomere number decrease of ~871 (28,955) following short-MTU training and an increase of ~947 (27,220) following long-MTU training. Serial sarcomere number changes of this magnitude may not have been pronounced enough to produce observable functional consequences in vivo, thereby not changing rFD or rFE.…”
Section: Why Did the Fascicle Length Adaptations Not Change Rfd Andmentioning
confidence: 84%
See 2 more Smart Citations
“…Lichtwark et al 47 determined a positive relationship between passive tibialis anterior fascicle length and sarcomere length; 2.64 µm is the average optimal sarcomere length 48 ; and 15° PF is close to the average optimal angle for dorsiflexion force production. 49 Based on these characteristics, the fascicle length adaptations (measured at 15° PF) in our study equated to a serial sarcomere number decrease of ~871 (28,955) following short-MTU training and an increase of ~947 (27,220) following long-MTU training. Serial sarcomere number changes of this magnitude may not have been pronounced enough to produce observable functional consequences in vivo, thereby not changing rFD or rFE.…”
Section: Why Did the Fascicle Length Adaptations Not Change Rfd Andmentioning
confidence: 84%
“…To date, no study has examined the modifiability of the history dependence of force through a training program longer than 4 weeks in duration or with isometric resistance training as the model to promote fascicle length adaptations. Furthermore, only one study 28 has employed the MTU length-specific isometric training model on the tibialis anterior to investigate muscle architectural adaptations. The data reported in the present study are part of that same larger training study, 28 with participants and muscle architecture data duplicated across publications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Some studies ( 11 13 ) reported that training-induced muscle hypertrophy was greater when trained at long versus short muscle lengths, but others ( 14 16 ) did not find a statistically significant difference. This discrepancy seems at least partly due to relatively small sample sizes ( n = 8–13 per condition) ( 11 16 ) and/or short intervention periods (6–8 wk) ( 11 14 , 16 ) of these studies.…”
mentioning
confidence: 99%
“…Some studies ( 11 13 ) reported that training-induced muscle hypertrophy was greater when trained at long versus short muscle lengths, but others ( 14 16 ) did not find a statistically significant difference. This discrepancy seems at least partly due to relatively small sample sizes ( n = 8–13 per condition) ( 11 16 ) and/or short intervention periods (6–8 wk) ( 11 14 , 16 ) of these studies. Importantly, the previous studies all adopted isometric ( 11 , 12 , 14 , 15 ) or partial range of motion ( 13 , 16 ) training at different joint angles about the same joint to compare long versus short muscle length conditions (e.g., knee flexed vs extended positions to train the quadriceps).…”
mentioning
confidence: 99%